2022
DOI: 10.48550/arxiv.2204.01742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snowmass White Paper: String Theory and Particle Physics

Abstract: We review recent developments and outstanding questions regarding connecting the top-down UV complete physical framework of string theory with the observed physics of the Standard Model and beyond the standard model physics, emphasizing the global nonperturbative framework of F-theory and general lessons from UV physics. This paper, prepared for the TF01 conveners of the Snowmass 2022 process, provides a brief synopsis of this important area, focusing on ongoing developments and opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 289 publications
(336 reference statements)
0
4
0
Order By: Relevance
“…Also, being armed with this knowledge about the entire ensemble of vacua may prove useful in understanding more refined statistics or searching for the needle-in-the-haystack that is the MSSM. See [52] for a recent summary of attempts to construct the MSSM in various corners of the string landscape. For example, machine learning approaches for sampling from this ensemble may be informed by which choices for the moduli allow for more solutions to the consistency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, being armed with this knowledge about the entire ensemble of vacua may prove useful in understanding more refined statistics or searching for the needle-in-the-haystack that is the MSSM. See [52] for a recent summary of attempts to construct the MSSM in various corners of the string landscape. For example, machine learning approaches for sampling from this ensemble may be informed by which choices for the moduli allow for more solutions to the consistency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…the program to realize our Universe in string theory, it has been a long-standing and primary goal to find the structure of the Standard Model (SM) of particle physics within the string landscape. While many (supersymmetric) string vacua have been identified that share many of the principal features of the Standard Model, there is as yet no single vacuum known in the string landscape that reproduces all the observed phenomenological details of our world; for recent reviews of work in this direction, see [2,3].…”
Section: Jhep05(2024)334mentioning
confidence: 99%
“…Efforts to connect string theory to elementary particle physics have a rich history, reviewed in [7] (where one can find many relevant references). A great deal of the effort in research to date has been focused on making tree-level supersymmetric solutions of string theory that realize N=1 supersymmetric models of (close to) realistic particle physics.…”
Section: String Theory and Particle Physicsmentioning
confidence: 99%